PENGARUH ELECTRONIC WORD OF MOUTH, CITRA MEREK, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN JASA MAXIM DI KOTA BEKASI - Rizka Fitri Ramadanty; Anna Wulandari (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
The changing times towards digitization are marked by increasingly rapid technological developments. With the development of technology, several companies are taking advantage of it to develop their companies into more creative businesses by taking oppurtunities to develop businesses in the field of information technology such as online transportation. This study aims to determine the effect of electronic word of mouth , brand image, and price perception, and brand image on purchasing decisions of maxim online transportation. The research data was obtained from the results of a questionnaire distributed to 100 respondents who live in Bekasi. Multiple linear regression analysis was performed using SPSS software. This study concludes that E-WOM have no effect on the decision to purchase maxim online transportation, while brand image and price perception has a positive effect on the decision to purchase maxim online transportation..